On the best means of giving increased facility to the transfer of land - Dobbs, Conway E. (Dublin Statistical Society, 1853)
Amongst all the various sources of national wealth, undoubtedly land is the one of most importance ; and though we may not be disposed to go the length of the school of French economists who regarded it as the only real wealth, and those employed in its cultivation as the only profitable labourers, still it is impossible not to regard it as the foundation and support of all others. It was in the surplus produce of the soil that manufactures first found its capital, and it was amongst those who owned that surplus that manufacturers found their purchasers. And if at the present day the enormous value of a foreign trade, and the accumulated wealth of our manufacturers have appeared to make those other sources of wealth apparent rivals to the land in the production of national prosperity, it must never be forgotten how precarious and uncertain their continued existence as such must ever be, when compared with the land.
A paper read before the Dublin Statistical Society, on Wednesday, February 23rd, 1853
Keywords: Land tenure; Land reform; 314.15